Optimising a targeted test reduction intervention for patients admitted to the intensive care unit: The Targeted Intensive Care Test Ordering Cluster Trial intervention. Issue 5 (September 2021) - Litton, Edward; Atkinson, Helen; Anstey, James; Anstey, Matthew; Campbell, Lewis T.; Forbes, Andrew; Hahn, Rebecca; Hooper, Katherine; Kasza, Jessica; Knapp, Sharon; McGain, Forbes; Ngyuen, Nhi; et al.
Abstract: Background: Approaches to routine diagnostic testing in the intensive care unit include time-scheduled testing and targeted testing. Blood tests and chest radiographs requested on a routine, time-scheduled basis may reduce the risk of missing important findings. Targeted testing, considering individual patient needs, may reduce unnecessary testing, wasted clinician time, and costs. However, existing evidence of targeted testing interventions is generally of low quality, and the optimal testing approach is uncertain. Objectives: The aim of the study was to describe the development of an intervention to reduce unnecessary diagnostic test ordering by clinicians working in intensive care, with the aim of informing the design of a pivotal clinical trial. Methods: The Capability, Opportunity, Motivation-Behaviour model was used as a theoretical framework for change. The intervention components were informed by systematically identifying, assessing, and classifying targeted testing interventions in behavioural terms. Feedback from intensive care clinicians and patients was sought using surveys and a consumer reference group. Results: The mean percentage of routine tests considered unnecessary by 201 intensive care clinicians was 33 (standard deviation = 16). When presented with a statement of the pros and cons for targeted versus liberal testing (n = 154), 93 (60%) consumer survey respondents preferred a more liberal approach, 33 (21%) preferred a more restrictive approach, and 28 (18%) were unsure. There were 24 behavioural interventions identified and incorporated into the final intervention. This had five major components: (i) a management committee to acquire, disseminate, and coordinate intervention-related information, (ii) a targeted testing guideline for sites, (iii) educational material for sites, (iv) site medical and nursing champions, and (v) site audit and feedback. Conclusions: Although surveyed intensive care clinicians report substantial unnecessary routine diagnostic testing, on the basis of currently available evidence, consumers prefer a more liberal approach. This feedback, and a framework to identify behavioural interventions, has been used to inform the design of a proposed targeted testing clinical trial.